Role of ligands in the formation, phase stabilization, structural and magnetic properties of alpha-Fe2O3 nanoparticles - Joshi, Satyawati S.; Patil, Prajakta R.; Nimase, Madhav S.; Bakare, P. P. (Journal of Nanoparticle Research, 2006)
The electrochemical synthesis of alpha Fe2O3 nanoparticles was performed using quaternary ammonium salts viz. TPAB, TBAB and TOAB in an organic medium by optimizing current density and molar concentration of the ligand. The role of ligands in the formation of alpha phase, structure and magnetic properties was investigated in details. The effect of increasing chain length on the particle size confirmed that as the chain length increases from propyl to octyl, the particle size decreases. X-ray diffraction spectra of as prepared samples and TEM analysis confirmed the amorphous nature of iron oxide. TEM showed beads of iron oxide joined together with a size distribution in the range of 6-30 nm. The Mossbauer studies also support this observation that for the lowest particle size, the line width is broader which successively reduces with increase in particle size. Iron oxide capped with TOAB indicated superparamagnetic nature at room temperature. The resultant internal magnetic field of 506 mm/s due to hyperfine splitting clearly established the formation of alpha-Fe2O3 The infrared spectroscopy and pH measurements revealed the binding of tetra alkyl ligand with iron oxide. The IR spectra and the increase in basicity of as prepared samples confirmed the formation of hydrated iron oxide. Above 800 degrees C the spectra indicated only iron oxide. Surface area obtained by BET method was 205 m(2)/g.
Keywords: Alkyl chain length; alpha-Fe2O3; Electrochemistry; magnetic properties; Nanoparticles; narrow size distribution

Nonaqueous synthesis and characterization of capped alpha-Fe2O3 nanoparticles from iron(III) hydroxy-oleate precursor - Chikate, Rajeev C.; Jun, Ki-Won; Rode, Chandrasekhar V. (Polyhedron, 2008)
The synthesis of capped alpha-Fe2O3 nanoparticles from thermal treatment of iron (III) hydroxy-oleate in boiling organic solvents around 250 degrees C with retention of the integrity of the oleate units during the reaction process is reported. The formation of capped iron oxide particles is accomplished under aerobic conditions while the solvents used in the synthesis have strong influence on the nature and morphology of nanoparticles. These nanoparticles are studied by means of X-ray powder diffraction, IR and XPS while the morphology and particle size of nanocrystals are evaluated using SEM and TEM analysis suggesting the formation of monocrystalline alpha-Fe2O3 particles having cubical and spherical morphologies with sizes ranging from 20 to 30 nm. This organophilic material with oleate capping around the surfaces can be readily dispersed in organic solvents thus forming organosols. These organosols exhibit band-edge emission photoluminescence band both in toluene as well as in solid state while FT-IR analysis reveals formation oleate capped nanoparticles The XPS data indicate ferric state having doublet from Fe 2P(3/2) and Fe 2p(1/2) core-level electrons. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: alpha-Fe2O3; capped nanoparticles; cubic morphology; ferrofluids; nonaqueous synthesis; Oleic acid; organosol